STK11 status and intussusception risk in Peutz-Jeghers syndrome. Issue 8 (1st August 2006) - Hearle, N; Schumacher, V; Menko, F H; Olschwang, S; Boardman, L A; Gille, J J P; Keller, J J; Westerman, A M; Scott, R J; Lim, W; Trimbath, J D; Giardiello, F M; et al.
Abstract : Background: Peutz-Jeghers syndrome (PJS) is caused by germline STK11 mutations and characterised by gastrointestinal polyposis. Although small bowel intussusception is a recognised complication of PJS, risk varies between patients. Objective: To analyse the time to onset of intussusception in a large series of PJS probands. Methods: STK11 mutation status was evaluated in 225 PJS probands and medical histories of the patients reviewed. Results: 135 (60%) of the probands possessed a germline STK11 mutation; 109 (48%) probands had a history of intussusception at a median age of 15.0 years but with wide variability (range 3.7 to 45.4 years). Median time to onset of intussusception was not significantly different between those with identified mutations and those with no mutation detected, at 14.7 years and 16.4 years, respectively (log-rank test of difference, χ 2 = 0.58, with 1df; p = 0.45). Similarly no differences were observed between patient groups on the basis of the type or site of STK11 mutation. Conclusions: The risk of intussusception in PJS is not influenced by STK11 mutation status.